NDM-1 Introduction in Portugal through a ST11 KL105 Klebsiella pneumoniae Widespread in Europe - Ângela Novais; Rita Veiga Ferraz; Mariana Viana; Paula Martins da Costa; Luísa Peixe (MDPI AG, 2022)
The changing epidemiology of carbapenem-resistant Klebsiella pneumoniae in Southern European countries is challenging for infection control, and it is critical to identify and track new genetic entities (genes, carbapenemases, clones) quickly and with high precision. We aimed to characterize the strain responsible for the first recognized outbreak by an NDM-1-producing K. pneumoniae in Portugal, and to elucidate its diffusion in an international context. NDM-1-producing multidrug-resistant K. pneumoniae isolates from hospitalized patients (2018-2019) were characterized using FTIR spectroscopy, molecular typing, whole-genome sequencing, and comparative genomics with available K. pneumoniae ST11 KL105 genomes. FT-IR spectroscopy allowed the rapid (ca. 4 h after incubation) identification of the outbreak strains as ST11 KL105, supporting outbreak control. Epidemiological information supports a community source but without linkage to endemic regions of NDM-1 producers. Whole-genome comparison with previous DHA-1-producing ST11 KL105 strains revealed the presence of different plasmid types and antibiotic resistance traits, suggesting the entry of a new strain. In fact, this ST11 KL105 clade has successfully disseminated in Europe with variable beta-lactamases, but essentially as ESBL or DHA-1 producers. We expand the distribution map of NDM-1-producing K. pneumoniae in Europe, at the expense of a successfully established ST11 KL105 K. pneumoniae clade circulating with variable plasmid backgrounds and beta-lactamases. Our work further supports the use of FT-IR as an asset to support quick infection control.